Correlation of Pancreatic Stone Protein (PSP) with Procalcitonin in Early-Onset Neonatal Sepsis (EONS) Patients - Desak Laksmi; I Nyoman Wande; Anak Agung Ngurah Subawa; Sianny Herawati; Ni Kadek Mulyantari; Ni Nyoman Mahartini; I Made Kardana (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Sepsis is defined as a systemic condition that arises from bacterial, viral or fungal infection, associated with hemodynamic changes and clinical findings that cause high morbidity and mortality. Neonatal sepsis that occurs 72 hours after birth is called early-onset neonatal sepsis (EONS). Procalcitonin is secreted by various tissues and is a marker of the acute phase of systemic reactions. Pancreatic stone protein (PSP) is a novel marker for identifying sepsis. High PSP levels are associated with more severe sepsis conditions. This analytical observational study aimed to determine the correlation between PSP levels and procalcitonin levels in patients with EONS. The study was conducted at the Clinical Pathology Laboratory of Ngoerah Hospital, Denpasar and the Integrated Biomedical Laboratory of the Faculty of Medicine, Udayana University from May 2024 to July 2024. The subjects in this study were 48 EONS patients undergoing treatment at Ngoerah Hospital who met the inclusion criteria. The results of the Spearman correlation test revealed a moderate correlation between PSP levels and procalcitonin levels in EONS patients (r = 0.581; p <0.001). Furthermore, multivariate analysis revealed that PSP levels significantly influenced procalcitonin levels after controlling for confounding variables (B = 0.137; 95% CI 0.101-0.174; p <0.001). These findings highlight the potential of PSP as a reliable marker in diagnosing sepsis and suggest that further exploration in this area could enhance our understanding of neonatal sepsis management.